2013
DOI: 10.1177/1470320313507121
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical expressions of natriuretic peptide receptor-C and neutral endopeptidase account for C-type natriuretic peptide decline during the progression of experimental obstructive nephropathy

Abstract: Introduction: C-type natriuretic peptide (CNP) selectively binds to the guanylyl cyclase coupled natriuretic peptide receptor (NPR)-B and exerts more potent antihypertrophic and antifibrotic properties. Elimination of CNP occurs mainly by neutral endopeptidase (NEP) and NPR-C. Methods:We established a rat model of unilateral ureteral obstruction (UUO) to examine the continuous change of the CNP expression and to assess the correlations of NPR-B, NPR-C, NEP with CNP in the obstructed kidneys. Results: The expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…Our recent in vivo study demonstrated that renal CNP expression tended to be higher within 24 hours after UUO and declined thereafter 6. The elevated expression of NPR-B may contribute to the overexpressed CNP in the early phase, whereas the sustained expression of NEP helps to, at least partly, account for the subsequent decline of CNP 34 35. However, the present study showed that NEP expression was significantly decreased after CNP treatment in MCs in vitro.…”
Section: Discussioncontrasting
confidence: 72%
“…Our recent in vivo study demonstrated that renal CNP expression tended to be higher within 24 hours after UUO and declined thereafter 6. The elevated expression of NPR-B may contribute to the overexpressed CNP in the early phase, whereas the sustained expression of NEP helps to, at least partly, account for the subsequent decline of CNP 34 35. However, the present study showed that NEP expression was significantly decreased after CNP treatment in MCs in vitro.…”
Section: Discussioncontrasting
confidence: 72%
“…30 Our previous study demonstrated that renal expressions of CNP mRNA and protein tended to be higher in the acute stage of TIF, but progressively declined in the advanced stage. 11 In this context, we hypothesize that CNP supplementation may be a promising strategy for the treatment of TIF.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, epithelial-mesenchymal transition, combined with the paradoxical expressions of NPR-C and neutral endopeptidase (NEP), may account for the decline of CNP in the advanced stages of nephropathies. 10,11 In contrast to regulation of blood pressure and body fluid homeostasis, the known physiological actions of CNP include local vasorelaxation, inhibition of organ remodeling, acceleration of reendothelialization, and antagonism of the reninangiotensin-aldosterone system. [13][14][15][16] Izumiya et al 17 examined the effects of exogenous CNP administration (0.05 mg/kg/min  2 weeks) on C57BL/6 mice with angiotensin II pretreatment, and found that angiotensin II-induced upregulation of collagen-I (Col-I), Col-III, and glyceraldehyde-3-phosphate dehydrogenase oxidase 4 in hearts was significantly suppressed by exogenous CNP infusion.…”
mentioning
confidence: 99%